From MAD to SAD: The Italian experience for the low‐frequency aperture array of SKA1‐LOW. Issue 3 (15th March 2016) - Bolli, P.; Pupillo, G.; Virone, G.; Farooqui, M. Z.; Lingua, A.; Mattana, A.; Monari, J.; Murgia, M.; Naldi, G.; Paonessa, F.; Perini, F.; Pluchino, S.; et al.
Abstract: This paper describes two small aperture array demonstrators called Medicina and Sardinia Array Demonstrators (MAD and SAD, respectively). The objectives of these instruments are to acquire experience and test new technologies for a possible application to the low‐frequency aperture array of the low‐frequency telescope of the Square Kilometer Array phase 1 (SKA1‐LOW). The MAD experience was concluded in 2014, and it turned out to be an important test bench for implementing calibration techniques based on an artificial source mounted in an aerial vehicle. SAD is based on 128 dual‐polarized Vivaldi antennas and is 1 order of magnitude larger than MAD. The architecture and the station size of SAD, which is along the construction phase, are more similar to those under evaluation for SKA1‐LOW, and therefore, SAD is expected to provide useful hints for SKA1‐LOW. Key Points: Italian demonstrators of low‐frequency aperture array for radio astronomy Aerial unmanned vehicle for the instrumental calibration of an aperture array Technological solutions implemented in the receiving chain of a low‐frequency aperture array